2019
DOI: 10.1590/1678-7757-2018-0434
|View full text |Cite
|
Sign up to set email alerts
|

3D comparison of dental arch stability in patients with and without cleft lip and palate after orthodontic/rehabilitative treatment

Abstract: This study aimed to compare the linear dimensions of the dental arches of adult patients with complete unilateral cleft lip and palate (UCLP) after orthodontic and prosthetic treatment with fixed partial dentures (FPD) to patients without clefts, using 3D technology. This retrospective longitudinal study sample consisted of 35 subjects divided into two groups. Included in this sample were 15 complete UCLP individuals who had received orthodontic treatment before rehabilitation with a fixed partial denture (FG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 24 publications
(26 reference statements)
0
17
0
2
Order By: Relevance
“…In individuals born without clefts, Class III was related to genetic variants associated with mandibular growth 28,29 and, in individuals born with clefts, the Class III may have been due to other genetic variants 18 and iatrogenic factors. 22,25 Although not significantly different, a shorter cranial base length was seen in 17 individuals born with UCLP and Class III compared to 10 individuals born with UCLP and Class I, which suggested that some UCLP cleft cases may have a Class III craniofacial configuration due mostly to a shortened cranial base. 30,31 No difference in the cranial base length between the UCLP Class III group and the non-cleft Class III group was found.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In individuals born without clefts, Class III was related to genetic variants associated with mandibular growth 28,29 and, in individuals born with clefts, the Class III may have been due to other genetic variants 18 and iatrogenic factors. 22,25 Although not significantly different, a shorter cranial base length was seen in 17 individuals born with UCLP and Class III compared to 10 individuals born with UCLP and Class I, which suggested that some UCLP cleft cases may have a Class III craniofacial configuration due mostly to a shortened cranial base. 30,31 No difference in the cranial base length between the UCLP Class III group and the non-cleft Class III group was found.…”
Section: Discussionmentioning
confidence: 82%
“…21 To study the Class III configuration of individuals born with cleft lip and palate more in detail, the Class III configuration in UCLP was compared to Class III individuals born without clefts and individuals born with UCLP with Class I malocclusion. If deficiency of facial growth only resulted from iatrogenic primary surgery repairs, [22][23][24][25] it was expected that the Class III pattern in individuals born with clefts would have a purely maxillary contribution with the other craniofacial characteristics showing normal values. These values should differ from those in individuals born without clefts or from a Class III configuration in an individual that had never been subjected to surgical repair.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on adult individuals with CLP and long-term studies on the stability of rehabilitation/prosthetic treatment comparing individuals with and without oral clefts [23] are lacking. The digitized casts obtained during the treatment phases can provide more information on the treatment stability of individuals with oral clefts.…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing the maxillary dimensions after rehabilitative treatment of adult individuals with and without oral clefts are lacking [23]. This information may help to better understand the relevant factors involving the complex rehabilitation of individuals with CLP and to determine parameters for protocols and future research.…”
Section: Introductionmentioning
confidence: 99%
“…Orofacial clefts are identified as congenital defects that occur during intrauterine life, precisely during the 8th week (cleft lip and alveolar flange) and the 12th week gestational age, when the palatine cleft occurs. 1 When the hygiene of these individuals is poor, they are susceptible to dental caries and all the harm it causes to the oral environment. When these patients are not assisted by a dentist, and interventions are not performed, the bacteria and their byproducts reach the pulp, and the tooth in question requires endodontic intervention.…”
Section: Introductionmentioning
confidence: 99%